X-Band Dielectric Resonator Bandpass Filter - Ain, M.F.; Ahmad, Z.A.; Othman, M.A.; Zubir, I.A.; Hutagalung, S.D.; Sulaiman, A. A.; Othman, A.K. (IEEE, 2010)
This paper presents a new approach of designing a bandpass filter by applying a combination of microstrip and cylindrical shape of dielectric resonators for X-Band application. Three dielectric resonators with a same permittivity and diameter of 60 and 5 mm respectively are applied in the circuit in order to obtain a wideband of more than 1.0 GHz. The interaction between the microstrip transmission line and dielectric resonators increases the coupling effect as well as minimizing the insertion loss in the filter passband. An analysis on the effect of the height of the dielectric resonators has been investigated in order to prove that the new approach contributes more advantages and viable at the desired application band.